"Will you draw me a pelvis?ˮ Dynamic neuro-cognitive imagery improves pelvic schema and graphic-metric representation in people with Parkinsonʼs Disease: A randomized controlled trial. (April 2019) - Abraham, Amit; Hart, Ariel; Dickstein, Ruth; Hackney, Madeleine E.
Highlights: No differences were detected between drawn pelvis height and width at base-line. The DNI group exhibited significantly greater improvements in pelvic schema and its graphic-metric representation. DNI could serve as a rehabilitation path for improving body schema in people with PD. Abstract: Background: Body schema (i.e., the mental representations of the body), vital for motor and cognitive functions, is often distorted in people with Parkinsonʼs disease (PD). Deficits in body, and especially pelvic, schema can further exacerbate motor and cognitive deficits associated with PD. Such deficits, including those in graphic and metric misjudgments, can manifest in drawing tasks. Mental imagery is a recommended approach for PD rehabilitation with potential for ameliorating body schema. Objective: To investigate the effect of a two-week dynamic neuro-cognitive imagery (DNI) training versus in-home learning and exercise control (learning/exercise) on pelvic schema and graphic representation (i.e., drawing height and width). Design: Twenty participants with idiopathic PD (Hoehn&Yahr I-III; M age: 65.75 ± 10.13) were randomly allocated into either a DNI or a learning/exercise group. Participants were asked to complete the "Draw Your Pelvisˮ test in which they drew their pelvis at pre- and post-intervention. Drawings were assessed for pelvic schema score and drawing dimensions (i.e., height and weight). Intervention: DNI anatomical and metaphorical imagery focusing on pelvic anatomy and biomechanics. Results: No difference ( p > .05) was detected at baseline between drawn pelvis height and width. Following intervention, improvements were greater in the DNI group for pelvic schema ( p < .01), drawn pelvic width ( p < .05) and width-height difference ( p < .05). Conclusions: This study suggests that DNI could serve as a rehabilitation path for improving body schema in people with PD. Future studies should explore DNI mechanisms of effect and the effect of enhanced pelvic schema on motor and non-motor deficits in this population.